Probing the relation between Theory of Mind and Epistemic Beliefs - Κυριακοπούλου, Νατάσσα; Βοσνιάδου, Στέλλα (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The present research investigated a) beliefs about the mind of others elementary school children’s (Theory of Mind), b) their epistemic beliefs about the nature of knowledge and knowing (Personal Epistemology), and c) the relationship between these two domains, in order to examine the hypothesis that Theory of Mind is a first step towards the development of a Personal Epistemology. Forty-six fifth graders were administered measures of their ability to attribute false beliefs to others and of their epistemic stance. The results showed statistically significant correlations between children’s ability to understand the beliefs of others and their epistemic beliefs. Furthermore, students performed better on Theory of Mind measures in relation to epistemic measures indicating that children more readily understand the constructivist nature of knowledge in the domain of Theory of Mind. The regression analyses carried out showed that Theory of Mind highly contributes to children’s epistemic stance.